EFL Students’ Intercultural Awareness in Genre-Based Writing Tasks - Nuraini, Hesty; Novitaningrum, Angella (PPPM STIT MIFTAHUL MIDAD, 2025)
This study aims to explore EFL students’ intercultural awareness as manifested in genre-based writing tasks. Employing a qualitative research design, the study involved undergraduate EFL students from Muhammadiyah University of Surabaya. Data were collected through students’ written texts, classroom observations, and semi-structured interviews. The data were analyzed using thematic analysis to identify patterns related to students’ intercultural awareness across different writing genres. The findings reveal that students demonstrated varying levels of intercultural awareness, particularly in their ability to incorporate cultural perspectives, address audience expectations, and apply genre conventions appropriately. While some students showed awareness of cultural differences in written expression, others tended to rely on local cultural frameworks, resulting in limited intercultural representation. The study also found that genre-based writing tasks provided meaningful opportunities for students to reflect on cultural values and practices within academic writing contexts. These findings suggest that genre-based writing instruction can serve as an effective pedagogical space for fostering intercultural awareness among EFL students. The study offers pedagogical implications for EFL writing instruction in higher education, particularly in multicultural and international academic contexts.